TANTANGAN DAN STRATEGI IMPLEMENTASI KURIKULUM MERDEKA DALAM PEMBELAJARAN AL-QUR’AN HADITS KELAS X DI MAN 2 PADANGSIDIMPUAN - Latifah Hanum (Ahsani Taqwim: Jurnal Pendidikan dan Keguruan, 2026)
This study aims to find out how the implementation of the Merdeka Curriculum in learning the subject of Qur'an Hadith in class X MAN 2 Padangsidimpuan. Merdeka Curriculum is a transformation of national education that emphasizes student-aligned learning, project-based learning, and strengthening character through the Pancasila Rahmatan lil 'Alamin Student Profile (P5RA). This study uses a descriptive qualitative method with data collection techniques through observation, teacher interviews, and document analysislearning. The results showed that the implementation of Merdeka Curriculum has been carried out by adjusting the Qur'an Hadith teaching module with a contextual approach, utilizing religious projects as a medium for internalizing Qur'an values, and implementing formative assessments to measure student learning achievements holistically. However, several obstacles such as limited teacher training and adaptation to teaching tools are still challenges in the implementation process. In general, the Merdeka Curriculum has a positive impact on students' motivation and active participation in learning Qur'an Hadith.